Imaging aortic valve calcification: significance, approach and implications. Issue 1 (January 2021) - Fletcher, A.J.; Singh, T.; Syed, M.B.J.; Dweck, M.R.
Abstract : Aortic stenosis is the most prevalent valvular heart disease worldwide, and rates are increasing with the growing and more elderly population. Although the precise mechanisms that underpin aortic valve stenosis are incompletely understood, pathological valvular calcification has emerged as a key instigator in mediating the biomechanical stiffening that can lead to symptoms, the need for aortic valve replacement, and death if left untreated. Here, we review the currently understood processes leading to aortic valve calcification, summarise the contemporary imaging assessments of valve calcification, and highlight how these might improve patient care and accelerate our pathological understanding and the development of an effective medical therapy.